The Effect of Group Counseling Services with Self Control Techniques on The Reduction of Smoking Behavior in Adolescents - Wahyungingtyas, Niken Tri; Purwati, P; Kurniati, Astiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effect of group counseling services with self-control techniques to reduce adolescent smoking behavior. This research is a type of pre-experimental research using the One Group Pretest- Posttest Design using one group of subjects with one type of treatment, namely the experimental group. The population in this study were male students of the Miftahurrohmah Islamic Boarding School, Majaksingi Village, Borobudur, Magelang, totaling 14 people. Many samples in this study were 6 people as the experimental group. Determination of the sample using purposive sampling. The data analysis method for hypothesis testing in this study for hypothesis testing in this study used a parametric Paired Sample t-test with the help of SPSS 24.0 for windows. The results of this study indicate that group counseling services with self-control techniques have a positive effect on reducing adolescent smoking behavior. This is evidenced by the results of the paired sample t-test with a significant (2-tailed) probability of 0.014 < 0.05. And based on the results of the analysis and discussion, there is an average score of the questionnaire on the adolescent smoking behavior scale of 28.03% from the pretest results and the posttest results of the adolescent smoking behavior questionnaire.